2018
DOI: 10.1039/c7gc03679e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient biosynthesis of enantiopure tolvaptan by utilizing alcohol dehydrogenase-catalyzed enantioselective reduction

Abstract: Using whole cells of Escherichia coli co-expressing alcohol dehydrogenase (PsADH) and formate dehydrogenase (CpFDH) in a biphasic aqueous–soybean oil system is shown to be an efficient method for the biosynthesis of enantiopure tolvaptan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The recombinant protein CpFDH from Candida parapsilosis C5 was purified by a purifier system (ÄKTA pure; GE Healthcare) with an affinity column filled with precharged Ni Sepharose™ (HisTrap HP; GE Healthcare, Piscataway, NJ, USA; Fig. S6) in our previous study (Zhang et al ., 2018). The activity of CpFDH was assayed by measuring the increase in absorbance at 340 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant protein CpFDH from Candida parapsilosis C5 was purified by a purifier system (ÄKTA pure; GE Healthcare) with an affinity column filled with precharged Ni Sepharose™ (HisTrap HP; GE Healthcare, Piscataway, NJ, USA; Fig. S6) in our previous study (Zhang et al ., 2018). The activity of CpFDH was assayed by measuring the increase in absorbance at 340 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Biocatalysts are increasingly used as efficient and environmentally safe alternatives than traditional catalysts in the production of fine chemicals, difficult to make using conventional organic catalysts. 4,[16][17][18][19] Mohammadi et al found that (S)-1-tetralol (S)-2 was obtained in 75% yield and 91% enantiomeric excess (ee) using Brassica oleracea whole-cell biocatalyst. 20 Similarly, Yadav et al reported that Daucus carota exhibited good performance in the asymmetric reduction of 1 to (S)-2 in terms of enantioselectivity (96% ee), but low conversion (70%) and yield (52%).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an important to conduct studies about asymmetric reduction of 1 using biocatalysts. Biocatalysts are increasingly used as efficient and environmentally safe alternatives than traditional catalysts in the production of fine chemicals, difficult to make using conventional organic catalysts 4,16–19 . Mohammadi et al found that ( S )‐1‐tetralol ( S )‐2 was obtained in 75% yield and 91% enantiomeric excess (ee) using Brassica oleracea whole‐cell biocatalyst 20 .…”
Section: Introductionmentioning
confidence: 99%